GAMBARAN FAKTOR-FAKTOR EKSTRINSIK YANG MEMPENGARUHI TERBENTUKNYA BATU GINJAL - Mardiah " "; Sofiana " Nurchayati; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract  Kidney stones is one of urinary tract disease that is caused by solid object at urinary tract. Factors that affecting the formation of kidney stones have to be known for recurrence  prevent and other complication. The purpose of this research was to know the overview of extrinsic factors that affecting the formation of kidney stones at Arifin Achmad Hospital Pekanbaru. The research design was descriptive study with restrospective approach. Samples were 30 patients that was taken by inclusion criteria that using consecutive sampling. The instrument was questionnaire about each variable. This research used univariate analysis to know distribution of frequencies. The result showed the most of patients environment have effected the formation kidney stones about 20 patienst (66,7%), the most of patients ensured adequate intake of fluid about 17 patients (56,7%), half of patients often consumed protein about 15 patients (50%), the most of patients consumed food containing calcium and phosphor about 16 patients (50,4%), the most of patients consumed food containing uric acid about 19 patients (63,3%), the most of patients consumed food with oxalate resource about 16 patients (53,3%), the most of patients often consumed food with citric acid resource about 16 patients (53,3%), and the most of patients about 17 patients (56,7%) had long sitting factor at work. The results of this study are expected to be the initial data to increase and develop the research that related the outside factors of the formation of kidney stones and  as inputs for students that will do further research. Keyword: Extrinsic Factors, Kidney Stones